DUAL PRACTICE, FACTORS AND SOLUTIONS FOR HEALTHCARE PROFESSIONALS - Milošević Gačević, Marijana (Srpski medicinski časopis Lekarske komore, 2023)
Dual practice is a phenomenon found in most countries, but it is noticeably more frequent in low-income countries, such as ours. It has been gaining more and more importance lately due to the fact that it may contribute to reducing the already insufficient number of professional health workers in healthcare systems. The reasons that lead to dual practice have not been sufficiently studied. Research results mainly point to economic factors as predictors, but apart from these factors, it is necessary to investigate the prevalence, real consequences, managing this phenomenon, as well as the assessment of the impact of policy measures implemented in this area. Although dual practice is seen as a possible systemic solution to issues such as limited resources (and revenues) in the public sector, low regulatory capacity and the interaction between market forces and human resources, if poorly regulated, it can lead to a conflict of interest as well as resource drain from the public to the private sector. An optimal regulation of the situation and the mobility of health workforce depends on the exceptional circumstances of the country, government capabilities, and the improvement of the health system. At the international level, governments react differently to the phenomenon of dual practice. To recognize the role of dual practice and mobility in the health workforce market, experts advocate more data on dual practice of healthcare workers and the need to integrate these data into national health workforce accounts. The need to develop a national health policy for monitoring dual practice in our country and to develop strategies for mitigating negative effects was highlighted. This paper analyzes the available literature on dual practice, the factors that influence the emergence of this phenomenon, and possible solutions for health workers.
Keywords: dual practice; health sector